The impact of teacher professional education program on improving teacher competences in Indonesia: A comparative study - Safrul Muluk; Azmil Hasan Lubis (Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the effect of the Teacher Professional Education Program (Program Pendidikan Profesi Guru, or PPG) on enhancing teacher competency in Indonesia. A quantitative approach was employed using a quasi-experimental design, comprising both experimental and control groups. The study population consisted of teachers across Indonesia, with the sample drawn from teachers in North Sumatra and Aceh Provinces through cluster random sampling. Observational techniques were utilized for data collection to ensure objective measurement of teacher competency. Descriptive statistical analysis revealed that the experimental group achieved a higher mean competency score compared to the control group, indicating superior performance among PPG participants. Furthermore, inferential analysis using an independent sample t-test yielded a significance value of less than 0.05 (p < 0.05), demonstrating a statistically significant difference in competency levels between teachers who had participated in the PPG program and those who had not. Based on these findings, it is concluded that the Teacher Professional Education Program exerts a significant positive effect on improving teacher competency in Indonesia. The program is therefore demonstrated to be an effective intervention for enhancing professional competence among Indonesian teachers. These results carry important implications for educational policy, suggesting that continued investment in PPG may contribute substantially to elevating national educational quality.